LOW HEAD PICO HYDRO UNIT USING LOW COST INDUCTION MOTOR AND WATER WHEEL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper presents a case study of employing a water wheel and a self excited induction generator combination for a Pico hydro generation unit. Simple procedure of designing a high speed water wheel is presented. A prototype Pico hydro generation unit is fabricated by authors. The unit was tested at actual site of low head water flow. Laboratory test results, on site test results and simulation results are presented. A remarkable agreement is observed between the laboratory and site tests. MATLAB simulation corroborates the field and laboratory findings. A check dam across a river in district Sangli of the state of Maharashtra, India is chosen for the field trials. The effective water head available round the year is 1 meter. Water discharge data has been obtained from the Department of Irrigation, State of Maharashtra.